Using climate information for priority setting and to target risk management and adaptation strategies in Africa - Stees, Jeannette van de; Kinyangi, J; Notenbaert, A; Thornton, P; Herrero, M (IOP conference series. Earth and environmental science (Online), 2009)
Keywords: openalex:import

Scoping climate change adaptation strategies for smallholder farmers in East Africa - a multi-dimensional, multi-scenario impact assessment. - Claessens, Lieven; Antle, J. M.; Stoorvogel, J.J.; Valdivia, R. O.; Thornton, P. K.; Herrero, M. (2015)
Abstract This chapter assesses the characteristics of current and future agricultural systems, land use, agricultural output, output price, cost of production, and farm and household size in response to climate change. This analysis also compared both current and projected future climate (2030), with and without adaptation, and for different socioeconomic scenarios (Representative Agricultural Pathways, RAPs) in two study areas in Kenya. A new approach to impact assessment, the Tradeoff Analysis Model for Multi-Dimensional Impact Assessment (TOA-MD) was adopted for this analysis, which simulated technology adoption and associated economic, environmental and social outcomes in a heterogeneous farm population for a regional impact assessment. These case studies yield new insights into the way that adaptation strategies could improve the livelihoods of smallholder farmers operating in the mixed crop-livestock systems in East Africa.
Keywords: openalex:import

Food production risks associated with land use change and climate change in East Africa - Moore, Nathan; Alagarswamy, G; Pijanowski, Bryan C.; Thornton, P; Olson, J; Lofgren, B; Andresen, J; Campbell, D (IOP Conference Series: Earth and Environmental Science, 2009)
Keywords: openalex:import

Food production risks associated with land use change and climate change in East Africa - Moore, Nathan; Alagarswamy, G.; Pijanowski, B.C.; Thornton, P. E.; Olson, J.; Lofgren, Brent M.; Andresen, Jeff; Campbell, David (IOP Conference Series: Earth and Environmental Science, 2009)
Keywords: openalex:import